IMPACTO DAS MUDANÇAS CLIMÁTICAS GLOBAIS NA DISPONIBILIDADE HÍDRICA DO SOLO NO ESTADO DO PARANÁ - Neves, Gabriela Leite (2015)
Climate change is a matter of research, since there are still many questions about its causes and consequences. The effects of climate change are diverse, and can reach from the biodiversity of the planet to the economic, social and environmental sectors. Thus the knowledge of climate variables, their changes and impacts on natural resources is very important. Many researchers already had observed that water, a natural resource of great value, may be disturbed due to climate change. Thus the study of water availability related to climate change becomes necessary. The aim of this study was to analyze the impact of possible climate changes on water availability in the state of Paraná, Brazil. It were used daily data of precipitation, and maximum and minimum air temperature of 28 locations, with series of data from 1980 to 2009. By means of the PGECLIMA_R tool daily weather data were simulated for the period 2010 to 2099, using the climate scenarios projected in the IPCC AR4-, IPCC AR5- and trend analysis of historical data from 1980 to 2009. For the creation of the latter scenario, there was a parallel study to obtain the changes in temperature for each location, which were then projected in the simulations. In order to quantify the water availability under the proposed conditions, we estimated the water balance for the current and simulated weather data using the methodology of Thornthwaite and Matter (1955). With interpolation tools, the results of changes in temperature and hydric indices obtained by the water balance were mapped for the entire state of Paraná. The hydric indices were then compared in different scenarios and analyzed periods. The results show that the state of Paraná has a great climate variability across regions. The trend analysis of air temperature pointed from reductions to increases in this variable and these were responsible for different impacts on water availability. In general, all scenarios were responsible for reductions in water availability, but the northern region is more susceptible to these reductions. The trend scenario showed reductions in water availability for most regions, but there was also increase in some specific regions of Parana State.